2014
DOI: 10.1016/j.ejpb.2014.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable nanoparticles composed of dendrigraft poly-l-lysine for gene delivery

Abstract: We developed novel gene vectors composed of dendrigraft poly-L-lysine (DGL).The transgene expression efficiency of the pDNA/DGL complexes (DGL complexes) was markedly higher than that of the control pDNA/poly-L-lysine complex. However, the DGL complexes caused cytotoxicity and erythrocyte agglutination at high doses.Therefore, γ-polyglutamic acid (γ-PGA), which is a biodegradable anionic polymer, was added to the DGL complexes to decrease their toxicity. The resultant ternary complexes (DGL/γ-PGA complexes) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
57
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 31 publications
3
57
1
Order By: Relevance
“…The toxicity is mainly caused by cations that can produce electrostatic attraction with anions on the surface of the cell membrane. 37 However, in the present study, this is not the case. The cationic amino groups have been blocked by covalent bonding of carboxyl groups on MNP-CA with amino groups on DGL.…”
Section: Results and Discussion Synthesis Of The Mnp-dgl-rgd-gx1-dox Npscontrasting
confidence: 54%
“…The toxicity is mainly caused by cations that can produce electrostatic attraction with anions on the surface of the cell membrane. 37 However, in the present study, this is not the case. The cationic amino groups have been blocked by covalent bonding of carboxyl groups on MNP-CA with amino groups on DGL.…”
Section: Results and Discussion Synthesis Of The Mnp-dgl-rgd-gx1-dox Npscontrasting
confidence: 54%
“…Among the polymers commonly employed as non-viral si-RNA delivery systems, chitosan (Ma et al, 2014;Ozpolat et al, 2014;Xie et al, 2014), poly(ethylene imine) (Urban-Klein et al, 2005;Nabzdyk et al, 2014), poly(amidoamine) dendrimers (Patil et al, 2008;Conti et al, 2014) and poly(L-lysine) (Inoue et al, 2008;Kodama et al, 2014) have been extensively investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Intravenous injection of γPGA is mainly accumulated in the spleen and liver in mice. Kodama et al reported that a ternary complex of pDNA/dendrigraft poly-L-lysine/γPGA ( Figure 5A) displayed high transfection ef iciency only in the spleen, although pDNA/dendrigraft poly-L-lysine polyplexes induced high transfection ef iciency in the liver, lungs, and spleen [80]. Furthermore, a ternary complex of pDNA/PEI/γPGA ( Figure 5A) was taken up by a γPGA-speci ic receptor-mediated energy dependent process [81], and they showed high transgene expression in the spleen without toxicity [82,83].…”
Section: Nucleic Acidmentioning
confidence: 99%
“…Anionic polymer or its conjugate Cationic polymer or liposome Reference pDNA ᵞPGA Chitosan [66,67] pDNA ᵞPGA Dendrigraft poly-L-lysine [80] pDNA ᵞPGA PEI [81][82][83] pDNA ᵞPGA Protamine [75] pDNA αPGA DOTAP/Chol liposome [54] siRNA ᵞPGA Chitosan [73] siRNA ᵞPGA Dendrigraft poly-L-lysine [74] siRNA αPGA DOTAP/Chol liposome [77] siRNA αPGA DMAPAP/DOPE liposome [78,79] siRNA ᵞPGA PEI [76] pDNA Heparin Cationic glycopolymer (Tr4) [84] pDNA Heparin-PEI - [85] pDNA Alginic acid, Pectin Lipofectamine 2000 [24] pDNA: plasmid DNA, siRNA: small interfering RNA, ᵞPGA: poly-ᵞ-glutamic acid, αPGA: poly-α-glutamic acid, PEI: polyethylenimine, DMAPAP: 2-{3-[bis-(3-amino-propyl)-amino]-propylamino}-N-ditetradecyl carbamoyl methylacetamide, Chol: cholesterol, DOPE: 1,2-dioleoyl-sn-glycero-3-phosphoethanolamine.…”
Section: Nucleic Acidmentioning
confidence: 99%